Schizodon unimaculatus, a new species from the lower Rio São Francisco with a reappraisal of the Schizodon species presenting a caudal-peduncle blotch (Teleostei: Anostomidae) - Garavello, Julio C.; Britski, Heraldo A.; Oliveira, Alexandre K.; Melo, Bruno F. (Zootaxa, 2024)
Schizodon unimaculatus new species, is described from the lower sections of the Rio São Francisco in northeastern Brazil. The new species differs from all known Schizodon species by the combination of presenting a subinferior mouth, a prominent dark brown blotch on the caudal peduncle, a dark brown longitudinal stripe along the lateral line, and three series of small dark dots horizontally aligned forming interrupted lines on the dorsal and middle regions of the trunk. It differs from congeners with a horizontal stripe and a dark blotch on the caudal peduncle, viz., S. knerii, S. rostratus, S. jacuiensis, S. nasutus, S. isognathus, S. altoparanae, S. vittatus, and S. trivittatus, by the combination of scale counts in lateral line and around caudal peduncle, color pattern, mouth position, and body proportions. The subinferior mouth additionally distinguishes the new species from S. knerii, S. jacuiensis, S. nasutus, S. altoparanae, S. platae, S. isognathus, and S. rostratus. Principal component and canonical variation analyses additionally distinguish the new species from S. knerii, S. altoparanae, and S. nasutus. We discuss the taxonomic history, relationships, and significance of mouth morphology, coloration, and meristic characters in taxonomic studies of Schizodon.